2013
DOI: 10.1038/ajg.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cyst Prevalence and the Risk of Mucin-Producing Adenocarcinoma in US Adults

Abstract: OBJECTIVES The presence of a pancreatic cyst often prompts concern, although the rate of malignant transformation to mucin-producing adenocarcinoma is not known. We aimed to determine the prevalence rate of mucin-producing adenocarcinoma in US adults with pancreatic cysts. METHODS This retrospective, population-based cross-sectional study calculated the annual number of mucin-producing adenocarcinomas using the Surveillance Epidemiology and End Results (SEER 18) database and the 2010 United States census. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
50
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 23 publications
5
50
1
2
Order By: Relevance
“…In our cohort of patients with pancreatic cysts, the incidence rate of malignant mucinous neoplasms was 0.7 per 1000 person-years. This is comparable to the reported prevalence rate of mucin-producing adenocarcinoma that arises in patients with pancreatic cysts, which is estimated to be 0.33 per 1000 patients (22). Pancreatic cysts have malignant potential, and several studies (14)(15)(16) in a Japanese population demonstrated an association between the pancreatic cysts and pancreatic ductal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 67%
“…In our cohort of patients with pancreatic cysts, the incidence rate of malignant mucinous neoplasms was 0.7 per 1000 person-years. This is comparable to the reported prevalence rate of mucin-producing adenocarcinoma that arises in patients with pancreatic cysts, which is estimated to be 0.33 per 1000 patients (22). Pancreatic cysts have malignant potential, and several studies (14)(15)(16) in a Japanese population demonstrated an association between the pancreatic cysts and pancreatic ductal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, several studies have demonstrated an association between pancreatic cysts and pancreatic ductal adenocarcinoma [7,[9][10][11][12]. Our results are in concordance with the literature, demonstrating 2.83 times higher odds of PDAC in patients with pancreatic cysts than in those without pancreatic cysts.…”
Section: Discussionsupporting
confidence: 95%
“…There has been a dramatic increase in the number of pancreatic cysts observed in the past two decades [18]. This increase has been so impressive that, at a certain point, it was not clear whether the appearance of some cystic lesions was a new epidemic or previously overlooked disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have been considered the most scientifically rigorous as regards the prevalence of pancreatic cysts in asymptomatic patients undergoing cross-sectional imaging [18]. The first study found a rate of 2.4% in 2803 consecutive patients undergoing abdominal MRI at an institute of preventive medical care in Germany [11].…”
Section: Discussionmentioning
confidence: 99%